Pupil size reflects successful encoding and recall of memory in humans - Kucewicz, Michal T; Dolezal, Jaromir; Kremen, Vaclav; Berry, Brent M; Miller, Laura R; Magee, Abigail L; Fabian, Vratislav; Worrell, Gregory A (Scientific reports, 2018)
Pupil responses are known to indicate brain processes involved in perception, attention and decision-making. They can provide an accessible biomarker of human memory performance and cognitive states in general. Here we investigated changes in the pupil size during encoding and recall of word lists. Consistent patterns in the pupil response were found across and within distinct phases of the free recall task. The pupil was most constricted in the initial fixation phase and was gradually more dilated through the subsequent encoding, distractor and recall phases of the task, as the word items were maintained in memory. Within the final recall phase, retrieving memory for individual words was associated with pupil dilation in absence of visual stimulation. Words that were successfully recalled showed significant differences in pupil response during their encoding compared to those that were forgotten - the pupil was more constricted before and more dilated after the onset of word presentation. Our results suggest pupil size as a potential biomarker for probing and modulation of memory processing.
Keywords: mladý dospělý; rozpomínání; Humans; lidé; Organ Size; Mental Recall; světelná stimulace; Female; Male; kognice; Adult; velikost orgánu; Healthy Volunteers; mužské pohlaví; ženské pohlaví; zdraví dobrovolníci pro lékařské studie; pupila; Photic Stimulation; Young Adult; Pupil; dospělí; Cognition